Tectonics, Climate, and Landscape Evolution 2006
DOI: 10.1130/s2006.2398(02)
|View full text |Cite
|
Sign up to set email alerts
|

From weather to climate—Seasonal and interannual variability of storms and implications for erosion processes in the Himalaya

Abstract: The extent to which orography may be a product of climate-erosion interactions is largely unknown. One grand challenge is to quantify the precipitation regimes of mountainous regions at the spatial and temporal scales relevant for investigating the interplay of erosion and tectonics in active orogens. In this paper, our objective is to synthesize recent research integrating numerical model simulations, satellite data, and surface observations in the Himalaya to elucidate the role of weather and climate in moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 39 publications
5
74
0
Order By: Relevance
“…The product combines TRMM 2B31, TRMM 2A12, special sensor microwave imager, advanced microwave scanning radiometer, advanced microwave sounding unit, and Climate Prediction Center infrared observations to estimate precipitation over low/mid-latitudes and is calibrated by station data. TRMM has documented deficiencies in capturing snowfall, which are especially problematic in HMA during winter (Lang and Barros 2004;Barros et al 2006;Maussion et al 2014). Because accurately quantifying total precipitation accumulation is difficult, our focus is on the timing and the relative precipitation contribution of WWD events, compared to all other dates.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The product combines TRMM 2B31, TRMM 2A12, special sensor microwave imager, advanced microwave scanning radiometer, advanced microwave sounding unit, and Climate Prediction Center infrared observations to estimate precipitation over low/mid-latitudes and is calibrated by station data. TRMM has documented deficiencies in capturing snowfall, which are especially problematic in HMA during winter (Lang and Barros 2004;Barros et al 2006;Maussion et al 2014). Because accurately quantifying total precipitation accumulation is difficult, our focus is on the timing and the relative precipitation contribution of WWD events, compared to all other dates.…”
Section: Datamentioning
confidence: 99%
“…The link between the atmosphere and glacial trends has also motivated studies on wintertime climate variability (Archer and Fowler 2004;Bhutiyani et al 2010;Dimri and Dash 2012;Palazzi et al 2013). In the KH, an excess of 50 % of the total annual precipitation is delivered by only a few westerly disturbances occurring between the months of December and March (Barros et al 2006). Winter westerly disturbances (WWD) are characteristically eastward propagating extratropical cyclones (Lang and Barros 2004;Barlow et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This was also observed in the CH composite, where moisture-laden flow from the Arabian Sea and Bay of Bengal encountered topography at near right angles. Barros et al (2006) showed through numerical simulation that low-level moisture laden flow approaching the CH lifts orographically to produce strong precipitation at steep angles of incidence.…”
Section: Atmospheric Mechanisms: Himalaya Heavy Precipitationmentioning
confidence: 99%
“…TRMM provides near-global 0.25° resolution precipitation estimates at 3-h intervals for the period (Huffman et al 2007Bookhagen 2010 Barros et al 2006). This inability to measure snowfall is particularly problematic for our study given that we are investigating high elevations during winter.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation